THE INCOME ANALYSIS AND PROFIT SHARING OF PUKAT PAYANG FISHERMAN IN KORONG PASIR BARU, NAGARI PILUBANG, SUNGAI LIMAU SUBDISTRICT, PADANG PARIAMAN REGENCY, WEST SUMATERA PROVINCE - Azni Marias Tuti; Hamdi Hamid; Darwis Darwis (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis study aims to measure, analyze and compare the income of pukat payang fisherman profit sharing based on these fisheries in Korong Pasir Baru Sungai Limau SubdistrictRegency Padang Pariaman by law No.1964 about 16 years for the results of the fishery. Determination of the respondent based on the purposive sampling technique with the respondent elected to as many as 15 people i.e. 5 fishermen owner, 5 fishermen helmsman and 5 people fisherman the crew.Research carried out using method survey with interview techniques. The Research showed that these pukat payang fishermen's income, at each different position.This can be seen from the median – median income of fishermen pukat payang profit sharing based on these local fishermen on the owner IDR.15.257.050, fisherman helmsman IDR.3.181.400 and the fisherman the crew of IDR.1.590.700while the median – median income of fishermen trawl these based on law No.1964 about 16 years for the results of the fishery owner fishers on the IDR 17.107.470fishermen helmsman IDR2.952.960 and the fisherman the crew of IDR.1.476.480.Keywords : Pukat Payang, Profit sharing, Income